Granito Serra Alta, província aurífera do Tapajós: petrografia e microscopia eletrônica de varredura - ARANTES, Letícia Briglia Ramos (2020)
The Serra Alta Granite (SAG) is represented by a batholith of approximately 35 km long by 1.0 km wide, elongated in the NW-SE direction and outcropping in the vicinity ofTocantinzinho River; it is wedged between rocks of the Cuiú-Cuiú Complex and Creporizão and Parauari suites. It is located in the central-north portion of the Tapajós Gold Province (TGP) in the easternmost portion of the Tapajós Domain (TJD), near the Iriri-Xingu Domain. The SAGis formed predominantly by isotropicsyenogranites and quartz syeniteof pink color, leucocratic to hololeucocratic, medium to coarse grainedessentiallyformed by alkali feldspar, quartz and plagioclase containing rare chloritizedbiotite and amphibole as varietal minerals; zircon, apatite,allaniteand opaque minerals are the main accessory phases. The SAG is correlated with syenogranites and feldspar-alkaline granites of the Maloquinha Intrusive Suite, which present Pb-Pb zircon crystallization age around 1.88 Ga and wide distribution in the TGP. Petrographic studies based on macroscopic and microscopic descriptions, besides analyzes of SEM/EDS allowed apreliminary separation of the granite in tree distinct petrographic facies: amphibole-biotite-syenogranite (ABSG),biotite-syenogranite (BSG), and amphibole-biotite-quartz-syenite (ABQS). The rocks of the ABSG and BSG faciesare most recurrent along the body, especially in its NW portion, while the rocks of ABQS faciesare restrict to central and SE portions of the body.